A Section Containing Selected Hadiths and Benefits from The Hearings of Ibn al-Shaykha (d. 799 AH) Takhrij by: Al-Hafiz al-Iraqi al-Hafiz. Study and Verification: جُزْءٌ فِيهِ أَحَادِيثُ عَوَالٍ وَفَوَائِدُ مُنْتَقَاةٌ مِنْ سَمَاعَاتِ الشَّيْخِ الْمُسْنِدِ أَبِي الْفَرَجِ عَبْدِ الرَّحْمَنِ بْنِ أَحْمَدَ بْنِ الْمُبَارَكِ الْغَزِّيِّ الشَّافِعِيِّ، الشَّهِيرِ بِابْنِ الشَّيْخَةِ، (المتوفى: 799هـ)، تَخْرِيجُ: الْحَافِظِ وَلِيِّ الدِّينِ أَبِي زُرْعَةَ أَحْمَدَ بْنِ الْحَافِظِ أَبِي الْفَضْلِ عَبْ - AbdelRahman ElSayed ElSayed AbdelGhaffar Balah (Civilization Research: Journal of Islamic Studies, 2026)
This research aims to investigate this precious hadith part, and its material of hadiths, narrations, and poems. In it, Abd al-Rahman bin Ahmad Ibn al-Sheikha, may God have mercy on him, the author of the part collected a number of hadiths, narrations, and poems that differ from his sheikhs, and are not specialized in a specific topic or issue. The part included and contained twenty-two hadiths, influences, and benefits. In his research, the researcher followed the inductive, descriptive, analytical, and critical approach, due to its suitability for this type of studies.